Enhancing organic vegetable farming through contract farming in Peninsular Malaysia - Ting, Jenn Ling (2016)
Due to globalization, market liberalization and consumers concern about food safety and environmental issues, there is an expansion in organic crops and livestock products demand from consumers. Malaysia has introduced organic farming through Malaysia Organic Standard since 2001. However, based on the record obtained from Department of Agriculture Malaysia, up to June 2014, there are only 72 (0.02%) organic farmers out a total of 272,000 farmers in Malaysia. This calls for the need to study why majorities of the farmers do not practice organic farming and also suggest possible solution such as contract farming as a motivating tools to enhance farmers’ intention to participate in organic farming. By adopting Theory Planned Behavior from Ajzen as conceptual framework, this study first find out the factors (independent variable) which influence farmers’ intention toward organic practice (dependent variable). Then, effect of contract farming as a moderator was tested for its motivational effect. Face to face interview was conducted using structured questionnaire to gather data from 329 conventional vegetable farmers in Peninsular Malaysia. Multiple regression analyze was used to identify factors that contributed to farmers’ intention on organic farming, while factor analyze was apply to group those factors with similar pattern of respond and Hierarchical Regression analyses was employed to examine the effect of contract farming as a moderator (motivational factor) in the relationship between the factors (predictors) and the farmers' intention (dependent variable). The results of this study indicates that there were four groups of factors which explain the farmers' intention towards practicing organic farming. These factors are farmers' attitude, perceived behavioral control, societal influence (subjective norm) and contract farming. The results of hierarchy regression indicates that there is relationship between farmers' attitude and their intention, however their intention will significantly improve by adding contract farming into the equation. Therefore contract farming plays a moderating role between attitude and intention. Perceived behavior control, does not show any significant relationship with intention to practice organic farming which indicates that since farmers do not have control over the situation, they are reluctant to practice organic farming. However by adding contract farming into the equation this relationship becomes not only positive but also significant which indicates contract farming will develop the control over the outcome by channeling farmers' products to the buyers. From the results it can be concluded vegetable farmers in Peninsular Malaysia are reluctant to practice organic farming due to lack of sales channel on organic products, although farmer do agree and are well informed about the benefits of organic farming such as better ex-farm price and more environment friendly, but the external factor especially selling and marketing to the right channels seem to be beyond their control. Hence, the results of the current research suggested that contract farming will be able to solve farmer' perceived barriers by giving them more control over the sales channel. Therefore in order to increase organic supply, Malaysia government should consider developing more contract farming which will ensure the farmers of the price, buyers and subsequently secure income.